Impact of Financial Literacy and Cognitive Biases on Individual Investment Decisions in Nepalese Stock Market - Dahal, Ramesh; Uprety, Pravat (Journal of Business and Social Sciences Research, 2025)
This study examines the factors that influence individual investors’ decisions in Nepal’s stock market, with a focus on cognitive biases (heuristic biases, framing effect, cognitive illusions, and herd mentality) and financial literacy. Structured questionnaires were used to collect data from 251 respondents in Kathmandu Valley, selected through purposive sampling to ensure participants had at least one year of investment experience. The data were analysed using descriptive and inferential statistics via the partial least squares structural equation modelling (PLS-SEM) method. The results show that behavioural biases have the greatest influence on investment decisions, followed by financial knowledge. While the study’s judgmental sampling and concentration on the Kathmandu Valley limit generalizability, and the use of self-reported data introduces possible biases, the findings are valuable. Financial advisers and policymakers might use these findings to develop educational programmes that promote financial literacy and risk management. Using Prospect Theory (Kahneman & Tversky, 1979) as the primary theoretical foundation, the study explores how investors’ perceptions of gains and losses influence their decision-making, often leading to irrational choices. Additionally, the Theory of Planned Behaviour (Ajzen, 1991) is used to explain how financial literacy shapes investment attitudes and perceived control over financial decisions.